Thermally stable near UV-light transparent and conducting SWCNT/glass flexible films. (November 2019) - Kukobat, Radovan; Kamijyou, Yuito; Stevic, Dragana; Furuse, Ayumi; Hayashi, Takuya; Sakai, Toshio; Neimark, Alexander V.; Kaneko, Katsumi
Abstract: Flexible single wall carbon nanotube (SWCNT) transparent and conducting films (TCFs) are indispensable to a further development of flexible electronics. Here we describe thermally and mechanically stable near-ultraviolet (near-UV) transparent and conducting films on ultrathin flexible glass produced from Zn/Al complex-SWCNT inks by bar coating. Our SWCNT/glass TCF is flexible and its relative resistance remains almost constant with increasing bending angle up to ∼170°. Sheet resistance decreases from 80 Ω/sq to 68 Ω/sq after heating in vacuum and increases from 80 Ω/sq to 300 Ω/sq after heating in air from 300 to 523 K. Transmittance in the near-UV region is in the range of 80–90% and does not change with increasing temperature up to 523 K. We believe that this SWCNT/glass TCFs should be promising for thermally stable transparent and flexible electronics. Graphical abstract: Image 1